THE MAISKOE MULTIMEGASTAGE DISSEMINATED GOLD-SULFIDE DEPOSIT (CHUKOTKA, RUSSIA): MINERALOGY, FLUID INCLUSIONS, STABLE ISOTOPES (O AND S), HISTORY, AND CONDITIONS OF FORMATION - Bortnikov N.S.; Bryzgalov I.A.; Krivitskaya N.N.; Prokof'ev V.Yu.; Vikentieva O.V. (My University, 2004)
A study of the sequence and stages of the mineral-forming processes, chemical compositions of sulfides, fluid inclusions, and sulfur isotopes in sulfides and oxygen isotopes in quartz of the Maiskoe deposit has been carried out. Three genetically different mineralization styles of various ages, which were formed in different geological and tectonic environments, have been superimposed at the Maiskoe deposit. Disseminated auriferous pyrite-arsenopyrite ores formed during the early gold-sulfide stage. Different mineral aggregates composing cassiterite-sulfide veins originated during the next rare metal stage. Quartz-stibnite veins formed during the final gold-stibnite stage. The following two types of fluid inclusions were found in quartz from different mineralization zones: (1) three-phase inclusions containing liquid, a vapor bubble (with liquid CO 2), and solid (halite, rarely two or three soluble phases); (2) three-phase inclusions containing liquid, a vapor bubble (without liquid CO 2), and solid (halite); (3) three-phase H 2O-rich inclusions with liquid CO 2; (4) three-phase vapor-rich inclusions; and (5) two-phase inclusions containing liquid and a vapor bubble. Three fluids of different compositions and physicochemical parameters are assumed to have been involved in the ore-forming system of the deposit. A H 2O + CO 2 + CH 4 fluid with a salt content of 8.2-2.2 wt % NaCl-equiv. deposited the economically valuable auriferous sulfide ores at 360-240°C and 1.1-0.9 kbars. A highly saline (37.5-30.0 wt % NaCl-equiv.) fluid and a low saline fluid formed the cassiterite-sulfide ores, which crystallized at a temperature of 500-170°C. The quartz-stibnite ores precipitated from an aqueous fluid with a salinity of 10.1-0.7 wt % NaCl-equiv. at 250-120°C. The δ 34S values for arsenopyrite and pyrite from the auriferous orebodies range from -6.9 to -0+.6 and -1.1 to-8.8%, respectively. The δ 34S values in sulfides from the cassiterite-sulfide mineralization are from -5.9 to -7.6 % for pyrite, -1.8 to +4.1% for sphalerite, -0.4 to-7.9% for galena, and -4.9 to -6.1% for sulfosalt minerals. The δ 34S values for stibnite vary from -9.9 to +0.8%. The δ 18O values of quartz from auriferous zones are from +11.8 to +14.5%, those of quartz from the veins formed during the cassiterite-sulfide megastage are from +1.7 to +4.1%, and those of quartz from the quartz-stibnite veins are from +12.2 to +15.2%. The ore formation conditions are assumed to have changed from mesoabyssal (the auriferous sulfide megastage) through shallow depth (the rare metal megastage) to subsurficial (the gold-stibnite megastage) environments. Fluids of magmatic origin and fluids originated at the heating of meteoric waters penetrated the hydrothermal system. The role of the latter fluids increased toward later megastages of this hydrothermal system.